The microstructural, textural, and mechanical effects of high-pressure torsion processing on Mg alloys: A review - Yan, Zhaoming; Zhu, Jiaxuan; Zhang, Zhimin; Wang, Qiang; Xue, Yong (Frontiers in Materials, 2022)
Magnesium (Mg) alloys attract considerable attention in the fields of aerospace, defense technology, and automobile production, owing to the advantages of their low density, their highly specific strength/stiffness, and their good damping and electromagnetic shielding performance. However, low strength and poor ductility limit further application. Severe plastic deformation is considered the most promising means of producing ultrafine-grained Mg alloys and improving their mechanical properties. To this end, high-pressure torsion (HPT) is one of the most effective techniques. This article outlines the microstructure, texture, and mechanical properties of Mg alloys processed using HPT. The effects of deformation parameters, such as processing temperature, turns, applied pressure, and rotation speed, on the grain refinement and secondary phases are discussed. Textural evolution is detailed in light of both intrinsic and extrinsic factors, such as cumulative strain and the composition of the alloy elements. The subsequent enhancement of mechanical properties and mechanisms, and the significant contribution of the HPT process to strength are further reviewed. Given the advantages of HPT for grain refinement and structural modification, researchers have proposed several novel processes to extend the industrial application of these alloys.